195 THE FATE OF THE ADJACENT SEGMENT FOLLOWING SPINAL FUSION FOR SPONDYLOLISTHESIS. (1st January 2006) - Kullar, R.; Talwar, V.; Gandhi, P.; Gupta, M.
Abstract : Purpose: Adjacent level degeneration (ALD) of the superior intervertebral disc following posterior lumbar interbody fusion (PLIF) for spondylolisthesis is a known potential consequence. We evaluated the adjacent segment for ALD and adjacent level fusion, or unintended extension of fusion beyond the site of spondylolisthesis, and correlated these findings to specific patient characteristics with a newly developed questionnaire. Methods: We retrospectively reviewed patient radiographs to determine ALD and adjacent level fusion. The intervertebral disc was considered degenerated if there was a 25% decrease in anterior and posterior disc height or greater than a 3 mm increase in listhesis from postop to follow-up. In addition, patients completed two questionnaires: (1) a standard Lumbar Core Questionnaire (AAOS) that focuses on subjective complaints of discomfort while performing daily activities and (2) a new questionnaire that focuses on a patient's comorbidities and their functional status. Between 1998 and 2004, we performed PLIF on 76 patients, and of this group, 75% of patients ( n = 57) returned their questionnaires and had appropriate follow-up radiographs. Results: The mean follow-up time was 21.2 months. Thirty-five percent had ALD, 37% had next to adjacent level degeneration, and 9% had degeneration at both levels. This is consistent with previous findings of a 50% chance of developing degeneration at either site. Additionally, 21% of patients had evidence of adjacent level fusion, and this group did not develop ALD ( p < .03). Furthermore, our new questionnaire was able to distinguish between patients that had developed ALD and those that had not (p < .0015). Less statistically significant differences were found using the standard Lumbar Core Questionnaire (p < .02). Conclusions: ALD may be a more frequent consequence than currently believed. In addition, adjacent level fusion may serve to protect against ALD. Moreover, the developed questionnaire may serve as a better tool to clinically evaluate risk of ALD than the Lumbar Core Questionnaire.